Ntino Ngasuh Cucung: Dari Kultural, Pola Asuh Tradisional Hingga Penyebab Stunting - Toni Heriawan; Azwar Azwar; Elfitra Elfitra (Indonesian Journal of Religion and Society, 2021)
This study aims to provide a new perspective in preventing stunting phenomena that occur in the community. This article is the result of a qualitative research conducted in Koto Tengah-Semurup, Kerinci Regency, Jambi Province. The data collection technique in this article uses in-depth interviews with a number of families whose children are stunted. The data in this article were analyzed using qualitative analysis starting from data reduction, data display to interpretation and drawing conclusions. The results of this study indicate that stunting is not only caused by the upbringing of a small family, but also the upbringing of an extended family, namely Ntino (grandmother). This parenting pattern arises because it is caused by the socio-cultural structure prevailing in society. With this socio-cultural structure, every child is raised with very traditional upbringing patterns, especially in diet. The conclusion of this article is that the occurrence of stunting is not only due to faulty parenting from the nuclear family, but also due to the social structure that gives birth to traditional parenting practices.